NMDA Receptors in the Rat Paraventricular Thalamic Nucleus Reduce the Naloxone-induced Morphine Withdrawal - Babaei, Fatemeh; Kourosh-Arami, Masoumeh; Farhadi, Mona (Central Nervous System Agents in Medicinal Chemistry, 2023)
Background: NMDA receptors have a significant role in the development of opioid physical dependence. Evidence demonstrated that a drug of abuse enhances neuronal excitability in the Paraventricular Nucleus (PVT). The current research studied whether blocking NMDA receptors through the administration of MK801 in the PVT nucleus could affect the development of Morphine (Mor) dependence and hence the behavioral indices induced by morphine withdrawal in rats. Methods: Male Wistar rats weighing 250-300 g were used. For induction of drug dependence, we injected Mor subcutaneously (s.c.) (6, 16, 26, 36, 46, 56, and 66 mg/kg, 2 ml/kg) at an interval of 24 hours for 7 days. Animals were divided into two groups in which the NMDA receptor antagonist, MK801 (20 mM in 0.1 ml), or its vehicle were applied into the PVT nucleus for 7 days before each Mor administration. On day 8, after injection of naloxone (Nal, 2.5 mg/kg, i.p.), withdrawal behaviors were checked for 25 min. Results: The current results demonstrated that the blockade of the NMDA receptor in the PVT nucleus significantly increased withdrawal behaviors provoked by the application of Nal in morphinedependent (Mor-d) rats. Conclusion: We concluded that the NMDA receptor in the PVT nucleus changes the development of Mor dependence.
Keywords: paraventricular nucleus